Gender, Migration and Citizenship across West African Frontiers as Portrayed in Selected (Yoruba) Nollywood Films - Adagbada, Olufadekemi (Advances in Social Sciences Research Journal, 2017)
Presently, being modern is associated with movement. As such, staying in one place may appear anachronistic. People move in search of better living conditions. In the past, trade was a major reason for migration. National and local tragedies like war, famine, economic mismanagement, political unrests and instabilities, have also brought about displacement and migration. Migration may be intra-state or inter-state. Sociologically, race, gender and other identity categories have always been vestiges of bias against, and domination of migrants, to exclude or marginalize them. My objective in this study is to examine the lot of the females as migrants within West African states as portrayed in selected (Yoruba) Nollywood films. Some of my findings are that the film producers do not highlight or bring to the fore, the importance of proper documentation about migrants; that the West African frontiers are porous; that language barriers affect the welfare of migrants and more essentially, female migrants’ worse condition in form of rape, forced labor, spousal violence and child care responsibilities. All these challenges are threats to the very purpose of ECOWAS. My suggestions are that there should be proper policing at the frontiers, that detailed and effective documentation and monitoring of the (few) individuals or group migrants that a country of refuge can conveniently cater for, be ensured. There should also be recognition and acceptance of certificates and diplomas possessed by any citizen of the ECOWAS state in any of the participating states. Financial aids can be given to unemployed migrants to become self-employed. Above all, forced displacement of persons must be drastically reduced by national leaders doing the needful politically, economically and socially, to improve the living conditions of their citizens.